Sustainable Urban Environments An Ecosystem Approach - van Bueren, Ellen M.; van Bueren, Ellen M.; van Bohemen, Hein.; van Bohemen, Hein.; Itard, Laure.; Itard, Laure.; Visscher, Henk.; Visscher, Henk. (Springer Netherlands : Imprint: Springer, 2012)
The urban environment – buildings, cities and infrastructure – represents one of the most important contributors to climate change, while at the same time holding the key to a more sustainable way of living. The transformation from traditional to sustainable systems requires interdisciplinary knowledge of the re-design, construction, operation and maintenance of the built environment. Sustainable Urban Environments: An Ecosystem Approach presents fundamental knowledge of the built environment. Approaching the topic from an ecosystems perspective, it shows the reader how to combine diverse practical elements into sustainable solutions for future buildings and cities. You’ll learn to connect problems and solutions at different spatial scales, from urban ecology to material, water and energy use, from urban transport to livability and health. The authors introduce and explore a variety of governance tools that support the transformation process, and show how they can help overcome institutional barriers. The book concludes with an account of promising perspectives for achieving a sustainable built environment in industrialized countries. Offering a unique overview and understanding of the most pressing challenges in the built environment, Sustainable Urban Environments helps the reader grasp opportunities for integration of knowledge and technologies in the design, construction and management of the built environment. Students and practitioners who are eager to look beyond their own fields of interest will appreciate this book because of its depth and breadth of coverage.